2011
DOI: 10.1016/j.cub.2011.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cortical Excitability in Grapheme-Color Synesthesia and Its Modulation

Abstract: SummarySynesthesia is an unusual condition characterized by the over-binding of two or more features and the concomitant automatic and conscious experience of atypical, ancillary images or perceptions [1–3]. Previous research suggests that synesthetes display enhanced modality-specific perceptual processing [4–7], but it remains unclear whether enhanced processing contributes to conscious awareness of color photisms. In three experiments, we investigated whether grapheme-color synesthesia is characterized by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 36 publications
15
82
0
2
Order By: Relevance
“…Most of the studies so far found that anodal stimulation improved human performance, while cathodal stimulation impaired human performance [14,19]. However, some exceptions to that, in which no e ect for cathodal stimulation or the opposite pattern (i.e., enhancement rather than impairment), were reported [20][21][22]. Jacobson et al [14] have attributed these inconsistencies to several possible mechanisms.…”
Section: Meet the Tes Familymentioning
confidence: 85%
“…Most of the studies so far found that anodal stimulation improved human performance, while cathodal stimulation impaired human performance [14,19]. However, some exceptions to that, in which no e ect for cathodal stimulation or the opposite pattern (i.e., enhancement rather than impairment), were reported [20][21][22]. Jacobson et al [14] have attributed these inconsistencies to several possible mechanisms.…”
Section: Meet the Tes Familymentioning
confidence: 85%
“…Enhanced excitability of the primary visual cortex in grapheme-colour synaesthetes was also demonstrated by TMS (Terhune et al 2011). These widespread differences in neuronal processing may be functionally relevant: enhanced perceptual ability is reported in synaesthetes (Banissy, Walsh and Ward, 2009) as well as more vivid imagery ͺ (Spiller, Jonas, Simner & Jansari, 2015) even for stimuli not implicated in their synaesthesia .…”
Section: Are Common Multisensory Interactions Generally Enhanced In Smentioning
confidence: 90%
“…Grapheme-colour synaesthetes (GCS) experience colours for letters and numbers. Not only do they have atypical visual-like experiences they also appear to have atypical (non-synaesthetic) visual functioning: they perform better at tests of colour discrimination (Banissy et al, 2013); show increased visual evoked potentials, in EEG, to high-frequency but not low-frequency Gabor gratings ; have lower phosphene thresholds to occipital lobe stimulation (Terhune, Tai, Cowey, Popescu, & Kadosh, 2011); and have been shown to have worse motion coherence (Banissy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%